Joseph Conrad : a life - Najder, Zdzisław (Camden House, 2007)
"Joseph Conrad is not only recognized as one of the world's great writers of English - and world - literature, but as a writer who lived a fascinating, unusually full and adventurous life. But Conrad's life presents the biographer with uncommon difficulty because, whether due to his itinerancy as a young man, the destruction of documentary evidence in the turmoil of the twentieth century, or the discreetness and relative isolation Conrad cultivated in his years as a writer, there are many periods for which documentation is difficult." "Zdzislaw Najder's meticulously documented biography first appeared in English in 1983, a product of twenty five years of painstaking study, and received great praise as the best, most complete biography of Conrad. Najder's command of English, French, Polish, and Russian allowed him access to a greater variety of sources than any other biographer, and this has again come into play in the present revised edition. It provides extensive new material, much of it unearthed to newly opened former east-bloc archives. Najder's Polish background and his own experience as an exile in the 1980s have afforded him an unmatched affinity for Conrad and his milieu." "There is new material on Conrad's father's genealogy and his role as a Polish national leader; Conrad's service in the French and British merchant marines; his early English reading and correspondence; his experiences in the Congo and their international context; the circumstances of writing A Personal Record and Under Western Eyes; and much more. In addition, several aspects of Conrad's life and works are more thoroughly and precisely analyzed: his problems with the English language; his borrowings from French writers; his attitude toward socialism; and his reaction to the reception of his books. New material makes up a quarter of the text of the revised edition and almost three-quarters of the references."--Jacket